2006
DOI: 10.1021/ol062642i
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Herbimycin A

Abstract: [structure: see text] Hsp90 has recently emerged as a promising biological target for treatment of cancer. Herbimycin A and other members of the benzoquinoid ansamycin class of natural products are known to inhibit Hsp90 activity. The total synthesis of herbimycin A was achieved from the commercially available Roche ester 1 by using allylmetals to control the stereogenic centers at C6, C7, C10, C11, and C12 and a ring-closing metathesis to control the (Z)-double bond of the (E,Z)-dienic moiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…[10] In order to demonstrate our method as a general entry into other 2-substituted-1,3-propanediols we chose to optimize our desymmetrization protocol on the next simplest 2-ethyl-1,3-propanediol 3, whose ester analog is not commercially available. Furthermore, the enzymatic desymmetrization of diol 3 has proven to be problematic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] In order to demonstrate our method as a general entry into other 2-substituted-1,3-propanediols we chose to optimize our desymmetrization protocol on the next simplest 2-ethyl-1,3-propanediol 3, whose ester analog is not commercially available. Furthermore, the enzymatic desymmetrization of diol 3 has proven to be problematic.…”
Section: Resultsmentioning
confidence: 99%
“…A significant advantage of using such synthetic processes is that both enantiomers of the desymmetrized product can be obtained from the same starting material by simply reversing the chirality of the desymmetrizing element. [10] Fukumoto and coworkers developed the first synthetic method to obtain desymmetrized 2-substituted-1,3-propanediols in high enantiomeric purity by employing chiral auxiliaries. [11,12] Oriyama and coworkers developed the first non-enzymatic catalytic desymmetrization using a proline-derived diamine to desymmetrize meso 2-alkyl-1,3-propane diols.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidation of 9 with Dess–Martin periodinane produced 3 in 88% yield. Similarly, the enantiomeric aldehyde 4 40 was synthesized from Roche ester 10 .…”
Section: Resultsmentioning
confidence: 99%
“…The molecule was termed herbimycin A due to its potent herbicidal activity against mono-and di-cotyledonous plants; this molecule also exhibits antifungal, anti-angiogenic and anti-tumor activities [22]. The absolute structure and configuration of HA was confirmed by Omura et al who reported that HA is a 19-membered macrocyclic lactam with seven stereogenic centers, a carbamate, an isolated tri-substituted (E)-double bond, and (E,Z)-diene and a benzoquinone ring system [111]. Structurally, this molecule resembles GA (Fig.…”
Section: Natural Product Macrocycle Hsp Inhibitorsmentioning
confidence: 99%
“…14), and it was logical to test its ability to modulate Hsp90, perhaps inhibiting its client proteins from binding to Hsp90, as well as its cytotoxicity against cancer cell lines. The first total synthesis of HA was reported in 1991 by Tatsuta et al [112], with other synthetic routes reported by Panek et al in 2004 [113] and Cossy et al in 2007 [111]. …”
Section: Natural Product Macrocycle Hsp Inhibitorsmentioning
confidence: 99%